Women and substance abuse: examining the factors influencing relapse - Razali, Asbah; Madon, Zainal; Hassan, Mohammed Salah (Research Institute of Asian Women Sookmyung Women's University, 2021)
Substance abuse in society is a source of concern, especially since it is spreading among women. Previously, substance abuse was associated with drug use by men, but today, women are increasingly involved as well. The purpose of this study is to determine the factors that influence relapse among female former addicts. This was a cross-sectional study of 50 former substance abusers, six months after receiving treatment at the Cure & Care Rehabilitation Centre. All respondents completed the questionnaires and the outcome was evaluated by the Statistical Package for the Social Sciences (SPSS). The results show a positive and significant relationship between family support and relapse (r = 0.183), and there is a positive and significant relationship between support from friends and relapse (r = 0.009). On the other hand, there is a significant but negative relationship between motivation and relapse (r = -0.387). There is also a significant negative relationship between self-esteem and relapse (r = -0.035). Women with drug addiction suffer from multiple stresses and a high risk of relapse and require significant social support from family and friends to resist the urge to relapse. It may be concluded that the inclination to relapse decreases when there is an increase in family and friend support, motivation, and self-esteem.